Removing Nasal Packing in Epistaxis: What to Do in the Case of an Undeflatable Foley Catheter Balloon - Gaspar-Sobrinho,Fernando Pena (2014)
Introduction  Undeflatable Foley catheter balloons adapted for use as nasal packing in epistaxis represent a possible complication. Case Reports  We report on three cases in which Foley catheter balloons adapted for use as posterior nasal packing in epistaxis failed to deflate. In one patient, deflation was achieved by simply using the fingertips to massage the segment of the catheter collapsed by the fixation device. In the second case, the Foley balloon was removed by the oral route after sectioning the catheter. In the third patient, the Foley catheter was successfully deflated after sectioning. Discussion  The probable causes of the undeflatable balloons in these cases were a blockage or lumen collapse of the balloon or a malfunction in the valve system. Although no definitive method has been established for dealing with this complication, the options proposed are the following: manipulation to restore the permeability of the segment of the catheter collapsed by the fixation device, if this is the case; sectioning the catheter or inserting a stiletto catheter; bursting the balloon; or removing it by the oral route. The latter option is apparently the most appropriate for the otolaryngologist in cases unrelated to simple collapse caused by the fixation device.